Remote Learning during the COVID-19 Pandemic: Evidence from a Three-Level Survey of Italian Schools - Andrea Caria; Adriana Di Liberto; Sara Pau (Institute of Labor Economics (IZA), 2024)
We used data collected during the COVID-19 pandemic to examine how Italian upper secondary schools organized their activities for remote learning (RL). We conducted a three-level survey, administering questionnaires to each institution's students (11th and 13th graders, 11,154 students), 3,905 teachers, and 105 principals. We describe how schools adjusted to the pandemic to ensure learning effectiveness during RL, how teachers and principals managed the transition from traditional to online teaching, and the perceptions of students, teachers, and principals regarding the effectiveness of RL. The analysis stresses Italian schools' challenges in changing teaching styles during RL and identifies individual and school-level inequality patterns. It also underscores a significant gap between teachers' perceptions of their digital skills and the actual use of ICT in class during RL activities. Results identify a positive and robust relationship between the student's perceptions of learning and other outcomes related to student success with the use of innovative teaching methodologies and appropriate organizational innovations, and the adoption of specific teachers' training.
Keywords: I21; I24; O33; 330; remote learning; COVID-19; socio-economic disparities